Quantifying diversity and growth form distribution of scleractinian corals, in Mangrove Bay, El Qoseir, Egypt - Theres Koch; Angelina Ivkić; Lewis Jones; Victor Scharnhorst; Constanze Stix; Antonia Auer; Theda Schöchtner; Gözde Özer; Simon Steinwender; Joseph Wallace Daurella; Martin Zuschin (Biodiversity Data Journal)
Coral reefs provide habitat for approximately 25% of all extant marine species, including 845 species of scleractinian corals. These rich ecosystems are becoming increasingly degraded in many regions by a range of anthropogenic factors, including recurrent bleaching episodes associated with rising sea surface temperatures. Within the northern Red Sea, coral reef communities appear to be faring relatively better than global trends and continue to exhibit remarkable diversity and thermal tolerance. However, recent reports of coral bleaching in the region highlight the urgent need for comprehensive ecological surveys to provide a baseline for long-term monitoring of biodiversity and potential species loss. This field report aims to support the tracking of diversity and growth form distributions of scleractinian corals at two reef sites at Mangrove Bay, El Qoseir, Egypt. Over time, it is our hope that such reports will contribute to broader databases and analyses focused on the biodiversity of reef-building coral species in the northern Red Sea.This study presents the first comprehensive checklist of scleractinian coral species (Scleractinia Bourne, 1900) in Mangrove Bay, El Qoseir, Egypt. As a result of our 2023 field survey, we identified a total of 68 species across 29 genera and 14 families, spanning six reef habitats — three per study site — at two study locations (sheltered and current-exposed), with depths ranging from 0 to 9.5 m. We found that both scleractinian coral diversity and coral growth forms varied amongst the six habitats. Branching corals were found in each habitat, but were particularly abundant at the current-exposed reef edge, where they covered 67% of the habitat. Encrusting and massive corals became more prevalent with increasing depth at both study sites, with massive corals covering 72% at the sheltered deeper reef slope and encrusting corals covering 24% at the current-exposed deeper reef slope. Species of the genus Porites dominated the sheltered site at all depths and the deeper reef slope at the current-exposed site, while Pocillopora verrucosa was most abundant at the exposed site’s reef edge and shallow slope.We provide photographs confirming these new records and access to the raw data on the abundance, distribution and conservation status of these taxa. Forty-three percent of the scleractinian species are classified as "Least Concern," but six are identified as "Vulnerable" (9%). Reef cover analyses revealed algae as the dominant group in most habitats, while scleractinian coral cover ranged between approximately 17% at the current-exposed reef edge and almost 35% at the current-exposed shallow reef slope. Millepora contributed the most at the exposed reef edge with nearly 28% cover, but was scarce elsewhere; soft corals exhibited their highest abundance on the deeper slope.Our observations serve as a critical baseline for future research and conservation efforts at Mangrove Bay by presenting an initial inventory of the local scleractinian communities and emphasise the importance of detailed species data in understanding and preserving coral reef ecosystems.